2021
DOI: 10.1097/nne.0000000000001065
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Engagement of Nursing Students in 2 Gamified Courses

Abstract: Background: Evidence suggests that gamification increases student engagement in course activities. However, student feedback about gamification in nursing contexts is needed. Purpose: The aim of this study was to describe nursing student perceptions of how gamification impacts student motivation and engagement. Methods: A convergent mixed-methods study was conducted. Surveys were completed by 58 first-year nursing students. Survey comments and data extracted from the learning management system were also collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…3 Research has found that students were more satisfied and engaged when study content included technology 4,5 and were more motivated and engaged when learning was gamified. 6 Evidence shows up to 80% of university students do not read the assigned materials. 7,8 For years, faculty have reported that students do not read all the assigned pages.…”
Section: Nurse Educatormentioning
confidence: 99%
See 2 more Smart Citations
“…3 Research has found that students were more satisfied and engaged when study content included technology 4,5 and were more motivated and engaged when learning was gamified. 6 Evidence shows up to 80% of university students do not read the assigned materials. 7,8 For years, faculty have reported that students do not read all the assigned pages.…”
Section: Nurse Educatormentioning
confidence: 99%
“…In addition, today's students who grew up with computers are technologically savvy and interested in more innovative ways of learning 3. Research has found that students were more satisfied and engaged when study content included technology4,5 and were more motivated and engaged when learning was gamified 6…”
mentioning
confidence: 99%
See 1 more Smart Citation